The Uses of Herbaria in Botanical Research. A Review Based on Evidence From Argentina - López, Alicia; Sassone, Agostina B. (Frontiers in Plant Science, 2019)
The Southern Cone encompasses ca. 16,700 vascular plant species, of which 60% are present in Argentina. To date, Argentina holds 3.5 million herbarium specimens stored at 47 active herbariums distributed in 16 out of 23 provinces (and the Federal District). Herbaria have unique advantages over other biological repositories such as germplasm banks or botanical gardens to produce good quality data for native flora conservation among other uses. Plant collections start early in the Argentine territory, long before the organization of the Republic. Since the 1700s, the European naturalists came in expeditions and collected the first Argentine specimens, which were sent abroad in order to identify them and are still stored at foreign herbaria. The relevance of the Natural Sciences was established early in the country. In 1812, Bernardino Rivadavia- who would later be considered the first President- commanded the creation of the first National Museum including an area dedicated to the herbaria. Since then, the Argentine botany emerged and settled down with strong influence of European naturalists, and nowadays, the active collectors store their materials in local herbaria such as BAB, CTES, SI, but the fluid international collaboration stimulates to send duplicates abroad (e.g. B, MBOT, NY). In this work, we overview the historical development of Herbaria and herbarium uses in Argentina since the consolidation of the nation-state. We also propose to perform today’s state-of-the-art, focusing on the current availability and the use of herbarium resources, through data mining and statistical analysis. As a result, and following the global tendency, we found that in Argentina, the discipline is threatened since represents only 5 % of the biologist. Our results suggest that the frequent uses of herbaria are taxonomy, systematics, genetics, and teaching. Between 1993 and 2018, we found that herbaria-based research has mainly been published in local journals, even though exist a gradual tendency to internationalize publications. More consulted herbaria resulted to be the larger and those which have digitized collections. Finally, we intend to bring a gender perspective insight to highlight the relevance of women in science.